CH3NH3PbI3 perovskite:poly(N-vinylcarbazole) blends for broadband optical limiting. Issue 4 (12th January 2017) - Bai, Ting; Dong, Ningning; Cheng, Hongxia; Cheng, Qing; Wang, Jun; Chen, Yu
Abstract : The superior optical limiting performance of the CH3 NH3 PbI3 perovskite: poly( N -vinylcarbazole) (weight ratio: 1 : 1) blends was experimentally studied in both DMF and in the PMMA matrix, respectively, by open aperture Z-scan method. Abstract : As one of the most active areas in laser protection, organic/inorganic hybrid functional materials have been expected to play an extremely important role in the field of optical limiting. The optical limiting performance of the CH3 NH3 PbI3 perovskite:poly( N -vinylcarbazole) (weight ratio: 1 : 1) blends (hereafter abbreviated as CP) was experimentally studied in DMF and in a poly(methylmethlacrylate) (PMMA) matrix, respectively, using an open aperture Z-scan method. In contrast to the CP dispersed in DMF, which showed no apparent nonlinear optical (NLO) response at both 532 and 1064 nm, after annealing at 200 °C in N2 for 30 min, a saturable absorption (SA) response was observed in the same DMF dispersion under the excitation of 532 nm laser. At 1064 nm, the annealed sample displayed different NLO responses: SA at the lower pulse energy and reverse saturable absorption (RSA) at the higher pulse energy. Both the 3 wt% and 6 wt% CP-doped PMMA composite films exhibited a typical RSA response, larger nonlinear absorption coefficient and superior optical limiting performance when compared to the same blends in DMF dispersion.